Training of Scientific Papers Writing On Students of Widya Dharma University - bayu purbha sakti (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2018)
This community service activities are done because the author wants students to have the ability to write their ideas to the public or community at large. The purpose of this activities is to provide skill to arrange scientific papers on students from Elementary School Teacher Education Study Program of Widya Dharma Univertsity by organizing scientific papers writing workshop. The benefits of this activities is to provide skills to students in preparing quality scientific papers and arrange forums to exchange ideas between the students and universities in terms of preparation for students in developing scientific papers. The method used is lecture method, discussion, answer question, and presentation. Several factors affecting the training activities of the scientific paper writing are the participants become interested to follow the training activities so that activities are expected to take place smoothly, this activities makes the participants to understand the scientific papers much better as important thing berfore they arrange the tesis, and the increased support and motivation from the Research and Community Service Institute of Unwidha so that future training activities can run smoothly. The manual book will be very necessary for students in arranging scientific papers so that students have scientific papers according to Unwidha’s papers. Unwidha lectures are expected to hold some student training so that students are more competents when they enter the workspace. The manual book will be very necessary for students in arranging scientific papers so that students have scientific papers according to Unwidha’s papers. Unwidha lecturers are expected to hold some student training so that students are more competent when they enter the workforce.